NTRK-Rearranged Uterine Sarcomas: Clinicopathologic Features of 15 Cases, Literature Review, and Risk Stratification. (20th October 2022) - Costigan, Danielle C.; Nucci, Marisa R.; Dickson, Brendan C.; Chang, Martin C.; Song, Sharon; Sholl, Lynette M.; Hornick, Jason L.; Fletcher, Christopher D.M.; Kolin, David L.
Abstract : NTRK -rearranged uterine sarcomas are rare spindle cell neoplasms that typically arise in the uterine cervix of young women. Some tumors recur or metastasize, but features which predict behavior have not been identified to date. Distinguishing these tumors from morphologic mimics is significant because patients with advanced stage disease may be treated with TRK inhibitors. Herein, we present 15 cases of NTRK- rearranged uterine sarcomas, the largest series to date. Median patient age was 35 years (range: 16 to 61). The majority arose in the uterine cervix (n=14) and all but 2 were organ-confined at diagnosis. Tumors were composed of an infiltrative, fascicular proliferation of spindle cells and most showed mild-to-moderate cytologic atypia. All were pan-TRK positive by immunohistochemistry (13/13); S100 (11/13) and CD34 (6/10) were usually positive. RNA or DNA sequencing found NTRK1 (10/13) and NTRK3 (3/13) fusions with partners TPR, TPM3, EML4, TFG, SPECC1L, C16orf72, and IRF2BP2 . Unusual morphology was seen in 2 tumors which were originally diagnosed as unclassifiable uterine sarcomas, 1 of which also harbored TP53 mutations. Follow up was available for 9 patients, of whom 3 died of disease. By incorporating outcome data of previously reported tumors, adverse prognostic features were identified, including a mitotic index ≥8 per 10 high-power fields, lymphovascular invasion, necrosis, and NTRK3 fusion. Patients with tumors which lacked any of these 4 features had an excellent prognosis. This study expands the morphologic spectrum of NTRK -rearranged uterine sarcomas and identifies features which can be used for risk stratification.